1993
DOI: 10.1017/s0890037x00027688
|View full text |Cite
|
Sign up to set email alerts
|

Soybean (Glycine Max) Tolerance and Sicklepod (Cassia Obtusifolia) Control with AC 263,222

Abstract: In field studies conducted under weed-free conditions, soybean yield was not adversely affected with POST applications of AC 263,222 at 18 g ha−1. At 36 g ha−1, soybean height at maturity was reduced in three of five studies and soybean yield in two of five studies. Application of 9 g ha−1of AC 263,222 to sicklepod at cotyledon to four-leaf (early POST) or at a maximum size of five-leaf (late POST) provided 30 to 48% control. Control was 54 to 73% with AC 263,222 at 9 g ha−1applied early POST followed by late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 7 publications
3
25
0
1
Order By: Relevance
“…Use of combinations of preemergent (PRE) and postemergent (POST) herbicides with POST cultivation is common in wide-row production systems in the midsouthern USA (Heatherly and Elmore, 1991;Poston et al, 1992;Oliver et al, 1993;Heatherly et al, 1994;Hydrick and Shaw, 1995;Askew et al, 1998). Herbicides banded over the crop row and cultivation of interrow areas can provide complementary weed control (Griffin et al, 1993;Newson and Shaw, 1996), and may result in lower weed management costs than for broadcast applications of herbicides (Krausz et al, 1995;Heatherly et al, 2001a) in any row spacing. Interrow cultivation alone will not control weeds over time, and will result in lower yield and net returns (Buhler et al, 1997) than when supplemented with herbicide weed control.…”
Section: -23 Postplant Tillagementioning
confidence: 99%
“…Use of combinations of preemergent (PRE) and postemergent (POST) herbicides with POST cultivation is common in wide-row production systems in the midsouthern USA (Heatherly and Elmore, 1991;Poston et al, 1992;Oliver et al, 1993;Heatherly et al, 1994;Hydrick and Shaw, 1995;Askew et al, 1998). Herbicides banded over the crop row and cultivation of interrow areas can provide complementary weed control (Griffin et al, 1993;Newson and Shaw, 1996), and may result in lower weed management costs than for broadcast applications of herbicides (Krausz et al, 1995;Heatherly et al, 2001a) in any row spacing. Interrow cultivation alone will not control weeds over time, and will result in lower yield and net returns (Buhler et al, 1997) than when supplemented with herbicide weed control.…”
Section: -23 Postplant Tillagementioning
confidence: 99%
“…1993). Also, AC 263,222 nlay cause unacceptable soybean injury (Griffin et al 1993;Miller and Griffin 1994;Newsome and Shaw 1994;Shaw 1991a, 1991b). Soybean height and yield have been reduced by AC 263,222 applied POST (Griffin et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Also, AC 263,222 nlay cause unacceptable soybean injury (Griffin et al 1993;Miller and Griffin 1994;Newsome and Shaw 1994;Shaw 1991a, 1991b). Soybean height and yield have been reduced by AC 263,222 applied POST (Griffin et al 1993). Wixson and Shaw (1991a) reported that all POST applications of AC 263,222 at 35 g ai/ha or more caused more soybean injury than metribuzin applied PRE followed by chlorimuron applied POST.…”
Section: Introductionmentioning
confidence: 99%
“…Use of combinations of PRE and POST herbicides with POST cultivation is common in WR production systems in the midsouthern USA (Askew et al, 1998; Heatherly and Elmore, 1991; Heatherly et al, 1993; Heatherly et al, 1994; Hydrick and Shaw, 1995; Oliver et al, 1993; Poston et al, 1992). Herbicides banded over the crop row and cultivation of interrow areas can provide complementary weed control (Newson and Shaw, 1996; Griffin et al, 1993) and may result in lower weed management costs than broadcast applications of herbicides (Krausz et al, 1995) in any row spacing. Interrow cultivation alone will not control weeds over time and will result in lower yield and net returns (Buhler et al, 1997) than when supplemented with herbicide weed control.…”
mentioning
confidence: 99%